Evaluation component structure of economic potential Carpathian region - Машіка, Г. (Київський національний університет імені Тараса Шевченка, 2016)
The economic potential of the region characterize its possible development; It is important to use the complex territorial resources, existing and future structure of its economy, geographical location; goal – improving the quality of life of the region. Purpose.Important research problems at present is the assessment component of the economic development of the region and identify potential development. Evaluation component structure of economic potential of the Carpathian region will improve the management of the region, the adoption of appropriate administrative decisions. Data&Methods. By itself, without the potential use of goal does not exist; investigating any potential always mean something which requires provisions and capabilities to achieve any result. Given this, and given the data of regional statistics to assess the structure of the economic potential of the Carpathian region we distinguish the following components: production capacity, investment and innovation potential, employment potential, financial potential. Results.To assess the production potential of the Carpathian region we used indicators: the volume of industrial products manufactured in the region; the volume of agricultural products;imports of goods and services are data on gross regional product. In 2015 there was a decrease of per formance to 10%. The investment potential of the region – a set of own and borrowed funds. In the Carpathian region the main source of funding for investments in fixed assets are own funds of enterprises and organizations. The employment potential of the region is reflected in the labor force. The Carpathian region has surplus manpower. In the last two years are significant problems with the formation of financial capacity. We believe you need to solve the problem of regional potential. To do this, select how increasing economic potential should be based on problem-oriented (targeted) estimates. For topical Carpathian region is the development of recreational areas. So we stopped at the eco-economic potential of the region. It is a combination of available natural resources and the natural environment. The Carpathian region has significant recreational, forestry, water resources; compared with other regions of Ukraine has a favorable environmental situation for the development of recreation and tourism, green tourism. Important economic value for the Carpathian region have environmental and economic factors: the landscape (take a large part of the Carpathian Mountains), geographical location, climate, resources, mineral water (336 sources).

В статті розглянуто наукові підходи до структури й оцінки господарського потенціалу регіону. Проаналізовані основні компоненти господарського потенціалу Карпатського регіону, зокрема, виділено виробничий, трудовий, інвестиційно-інноваційний та фінансовий потенціал. Досліджено показники, які характеризують дані компоненти структури господарського потенціалу Карпатського регіону. Звертається увага на необхідність проблемно-орієнтованої (цільової) оцінки структури господарського потенціалу; у цьому зв’язку виділяється екологічно-економічний потенціал, як такий, що відкриває нові перспективи для розвитку Карпатського регіону.
Оцінка компонентної структури господарського потенціалу Карпатського регіону
Hedz, M. Y. (2012), Sutnist ta struktura sotsialno-ekonomichnoho potentsialu modernizatsii rehioniv [The essence and structure of social and economic potential of upgrading the Regions], Finansovyi prostir, No. 2, pp. 33-38. [in Ukrainian] S. V. (2006), Vplyv rozshyrennia vnutrishnoho rynku na ekonomichne zrostannia Ukrainy [The impact of the expansion of the internal market on economic growth Ukraine], Stratehichni priorytety, No. 1, pp. 93-101. [in Ukrainian] Derzhavna sluzhba statystyky Ukrainy [State Statistics Service of Ukraine]. Availabl eat: http://www.ukrstat.gov.ua [in Ukrainian] Lysa, O. I. (2013), Otsinka ta porivniannia rivnia modernizatsii osnovnykh zasobiv u Zakhidnomu rehioni Ukrainy [Evaluation and comparison of the modernization of fixed assets in Western Ukraine], Ekonomichnyi visnyk Donbasu, No. 3 (33), pp. 115-119. [in Ukrainian] Lutskiv, O. M. (2013), Rehionalni osoblyvosti ctrukturno-tekhnolohichnyk htransformatsii promyslovosti [Regional features structural and technological transformation industry], Innovatsiinaekonomika, No. 2, pp. 97-101. [in Ukrainian] Myronenko, M. Yu. Orhanizatsiini aspekty upravlinnia ekonomichnym potentsialom rehionu [Organizational aspects of the economic potential of the region], Derzhavne upravlinnia: udoskonalennia ta rozvytok [Public administration, improvement and development]. Available at: http://www. dy.nayka.com.ua [in Ukrainian] Semenov, V. F. (2008), Rehionalna ekonomika: navch. posibn. [Regional economy: teach. posibn],Kyiv: Lesia, 595 p. [in Ukrainian] Stechenko, D. M. (2006), Rozmishchennia produktyvnykh syl i rehionalistyka: pidruch. [Placement of the productive forces and regionalism: textbook], Kyiv: Vikar, 396 р. [in Ukrainian] Tyshchenko, A. N., Kyzym, N. A., Kubakh, A. Y., Davyskyba, E. V. (2005), Ekonomycheskyi potentsyal rehyona: analyz, otsenka, dyahnostyka: Monohrafyia [The economic potential of the region: the analysis, evaluation, diagnosis: Monograph], Kharkov: YNZhEK, 176 р. [in Ukrainian] Shevchuk, Ya. V., Tsenkler, N.I. (2014), Resursne zabezpechennia ta otsiniuvannia okremykh vydiv ekonomichnoi diialnosti Karpatskoho rehionu [Resource provision and evaluation of individual economic activity Carpathian region],Naukovyi visnyk NLTU Ukrainy, vol. 24.10, pp. 300-306. [in Ukrainian] Shpenyk, T. K. (2013), Analiz sotsialno-ekonomichnoho stanu Zakarpatskoi oblasti z tochky zoru rozvytku turystychnoi haluzi [Analysis of socio-economic status Transcarpathian region in terms of tourism development], Naukovyi visnyk Uzhhorodskoho universytetu, No. 2, pp. 34-39. [in Ukrainian]
Keywords: Карпатський регіон; господарський потенціал; структура; компоненти; оцінка; виробничий потенціал; трудовий потенціал; інвестиційно-інноваційний потенціал; фінансовий потенціал; екологічно-економічний потенціал; Carpathian region; economic potential; structure; components; evaluation; production capacity; working capacity; investment and innovation potential; financial potential; ecological and economic potential